2003
DOI: 10.1113/jphysiol.2003.045799
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nitric Oxide Synthase by L‐NAME Speeds Phase II Pulmonary V̇O2 Kinetics in the Transition to Moderate‐Intensity Exercise in Man

Abstract: There is evidence that the rate at which oxygen uptake (.VO2) rises at the transition to higher metabolic rates within the moderate exercise intensity domain is modulated by oxidative enzyme inertia, and also that nitric oxide regulates mitochondrial function through competitive inhibition of cytochrome c oxidase in the electron transport chain. We therefore hypothesised that inhibition of nitric oxide synthase (NOS) by nitro-L-arginine methyl ester (L-NAME) would alleviate the inhibition of mitochondrial .VO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
75
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 50 publications
5
75
3
Order By: Relevance
“…This is consistent with our laboratory's previous reports that the p was significantly faster when NOS activity was inhibited by L-NAME (38,39,66). The p was also slightly longer during moderate exercise (group mean p 29 vs. 26 s for BR and PL), but this difference was not statistically significant.…”
Section: Effects Of Dietary Nitrate On Bpsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with our laboratory's previous reports that the p was significantly faster when NOS activity was inhibited by L-NAME (38,39,66). The p was also slightly longer during moderate exercise (group mean p 29 vs. 26 s for BR and PL), but this difference was not statistically significant.…”
Section: Effects Of Dietary Nitrate On Bpsupporting
confidence: 91%
“…The inhibition of NO synthesis has previously been shown to increase steady-state V O 2 in dogs (56), but not humans (38) or horses (41). It is widely accepted, however, that NO is involved in the regulation of mitochondrial O 2 consumption.…”
Section: Effects Of Dietary Nitrate On Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…An administration of β-adrenergic blockade slows down the O 2 on-kinetics in humans [41], whereas an administration of L-NAME, causing an inhibition of nitric oxide synthase, significantly accelerates the O 2 on-kinetics in a thoroughbred horse [42], as well as in humans [43,44]. The authors concluded that the intrinsic inertia of oxidative metabolism at the onset of heavy-intensity exercise may result from an inhibition of mitochondrial respiration by nitric oxide.…”
mentioning
confidence: 99%
“…The discussed findings indicate that the rate of oxygen uptake at the onset of exercise may be affected by the interventions contributing to oxygen delivery to the working muscles (especially at high-power output exercise) [37,38,40] and the factors affecting the rate of muscle metabolism [41][42][43][44]16].…”
mentioning
confidence: 99%